WHAT SHOULD BE THE MODERN ENGINEERING EDUCATION (THINKING OF GLOBAL FORUM PARTICIPANTS) - Vyacheslav M. Prikhod’Ko; Alexander N. Solovyev (Высшее образование в России)
The different points of view presented at the World Engineering Education Forum (WEEF 2014) are discussed. The subjects of discussion in this paper are as follows: what should be in our day objectives, content, methods of teaching and learning tools, as well as methods for assessing educational achievements in engineering education. We have distinguished the dominant points of view: the goal is to prepare engineers able to create and implement projects under the ideas of «sustainable development», the content is determined by a multidisciplinary educational programmes designed taking into account the views of all interested parties, the main idea of the methods - student-oriented approach, wide using of e-learning, m-learning, evaluation of educational achievements in terms of developing the necessary competencies.